Acute impact of drinking coffee on the cerebral and systemic vasculature. Issue 10 (19th May 2017) - Washio, Takuro; Sasaki, Hiroyuki; Ogoh, Shigehiko
Abstract: Previous studies have suggested that the risk of ischemic stroke increases immediately after drinking coffee. Indeed, drinking coffee, that is, caffeine, acutely increases arterial stiffness as well as blood pressure and peripheral vascular resistance. On the other hand, it has been reported that arterial stiffening is associated with elevation in the pulsatility index (PI) of cerebral blood flow (CBF), which increases the risk of brain disease. However, the effect of drinking coffee on the PI of the CBF and its interaction with arterial stiffness remain unknown. Against this background, we hypothesized that an acute increase in arterial stiffness induced by drinking coffee augments cerebral pulsatile stress. To test this hypothesis, in 10 healthy young men we examined the effects of drinking coffee on the PI of middle cerebral artery blood velocity (MCAv) and brachial‐ankle pulse wave velocity (baPWV) as indices of cerebral pulsatile stress and arterial stiffness, respectively. Mean arterial blood pressure and baPWV were higher ( P  < 0.01 and P  = 0.02), whereas mean MCAV and mean cerebrovascular conductance index were lower upon drinking coffee ( P  = 0.02 and P  < 0.01) compared with a placebo (decaffeinated coffee). However, there was no difference in the PI of MCAv between drinking coffee and the placebo condition. These findings suggest that drinking coffee does not increase cerebral pulsatile stress acutely despite an elevation in arterial stiffness in the systemic circulation. Abstract : The pulse cerebral blood flow and the pulsatility index of cerebral blood flow did not increase immediately after drinking coffee, despite an increase in arterial stiffness.